Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This note presents estimates of potential growth and the output gap in Latvia. The estimates suggest that the output has marked below potential in the early 2000s but the output gap becomes positive and large after EU accession. With unemployment still well above its natural level, the output gap is estimated to be negative in 2012, but is expected to narrow gradually and be closed in the next 3-4 years. Potential growth is expected to be substantially lower than in 2002-07.